环保型捆钞机送切胶机构的研究与设计 - 曹巨江; 吕凯归; 王映俊; 钱德明; 陈均志 (Jixie chuandong)
Based on the paper tape of environment-friendly packing bank machine,the matched mechanism to send and cut the paper tape is designed.The hot cement is thin and elastic,using the same cutting tool as cutting paper belt can’t snip the belt,and cut hot cement tape smoothly.The hot cement is easy to cohere in high temperature,so the release film is put on the surface before leave factory.Therefore,we must try to wipe off it before glued.According to the requirements above,scald and cut mechanism which could achieved cutting action and accurate positioning on the paper belt is designed,thus it could accomplish fixed point and fixed amount gluing.After that,the cutting tool retraced,and the interfering between cutting tool and follow-up action is avoided.